Transmission line compensation for power system stability improvement / Muhamad Qamarul Hafiz Abdullah - Abdullah, Muhamad Qamarul Hafiz (2009)
This paper presents the transmission line compensation to improve the system stability in power system. In order to achieve the objective, three methods of line compensation were implemented, series capacitor, shunt capacitor and shunt reactor to improve the voltage stability by looking at the voltage regulation. The location of weakest transmission line was identified using the sensitivity index (SI). The proposed method was applied to a 30 busbar IEEE systems to show its feasibility and capability. All simulation was done using the MATLAB version 7.5 programming.